Congenital tremor and splay leg in piglets – insights into the virome, local cytokine response, and histology - Hedvig Stenberg; Stina Hellman; Lisa Lindström; Magdalena Jacobson; Caroline Fossum; Juliette Hayer; Maja Malmberg (BMC Veterinary Research, 2022)
Abstract Background Atypical porcine pestivirus (APPV) is a neurotropic virus associated with congenital tremor type A-II. A few experimental studies also indicate an association between APPV and splay leg. The overarching aim of the present study was to provide insights into the virome, local cytokine response, and histology of the CNS in piglets with signs of congenital tremor or splay leg. Results Characterization of the cytokine profile and virome of the brain in piglets with signs of congenital tremor revealed an APPV-associated upregulation of Stimulator of interferon genes (STING). The upregulation of STING was associated with an increased expression of the gene encoding IFN-α but no differential expression was recorded for the genes encoding CXCL8, IFN-β, IFN-γ, IL-1β, IL-6, or IL-10. No viral agents or cytokine upregulation could be detected in the spinal cord of piglets with signs of splay leg or in the brain of piglets without an APPV-infection. The histopathological examination showed no lesions in the CNS that could be attributed to the APPV-infection, as no difference between sick and healthy piglets could be seen. Conclusion The results from this study provide evidence of an APPV-induced antiviral cytokine response but found no lesions related to the infection nor any support for a common causative agent.